A Comprehensive Analysis of SE-lncRNA/mRNA Differential Expression Profiles During Chondrogenic Differentiation of Human Bone Marrow Mesenchymal Stem Cells - Jiang, Yu; Zhang, Chen; Long, Lujue; Ge, Lihua; Guo, Jing; Fan, Zhipeng; Yu, Guoxia (Frontiers in Cell and Developmental Biology, 2021)
Objective: Articular cartilage injury is common and difficult to treat clinically because of the characteristics of the cartilage. Bone marrow-derived mesenchymal stem cells (BMSCs)-mediated cartilage regeneration is a promising therapy for treating articular cartilage injury. BMSCs differentiation is controlled by numerous molecules and signalling pathways in the microenvironment at both the transcriptional and post-transcriptional levels. However, the possible function of super-enhancer long non-coding RNAs (SE-lncRNAs) in the chondrogenic differentiation of BMSCs is still unclear. Our intention was to explore the expression profile of SE-lncRNAs and potential target genes regulated by SE-lncRNAs during chondrogenic differentiation in BMSCs. Materials and Methods: In this study, we conducted a human Super-Enhancer LncRNA Microarray to investigate the differential expression profile of SE-lncRNAs and mRNAs during chondrogenic differentiation of BMSCs. Subsequent bioinformatic analysis was performed to clarify the important signalling pathways, SE-lncRNAs, and mRNAs associated with SE-lncRNAs regulating the chondrogenic differentiation of BMSCs. Results: A total of 77 SE-lncRNAs were identified, of which 47 were upregulated and 30 were downregulated during chondrogenic differentiation. A total of 308 mRNAs were identified, of which 245 were upregulated and 63 were downregulated. Some pathways, such as focal adhesion, extracellular matrix (ECM)-receptor interaction, TGF-β signalling pathway, and PI3K-Akt signalling pathway, were identified as the key pathways that may be implicated in the chondrogenic differentiation of BMSCs. Moreover, 5 potentially core regulatory mRNAs (PMEPA1, ENC1, TES, CDK6, and ADIRF) and 37 SE-lncRNAs in chondrogenic differentiation were identified by bioinformatic analysis. Conclusion: We assessed the differential expression levels of SE-lncRNAs and mRNAs, along with the chondrogenic differentiation of BMSCs. By analysing the interactions and co-expression, we identified the core SE-lncRNAs and mRNAs acting as regulators of the chondrogenic differentiation potential of BMSCs. Our study also provided novel insights into the mechanism of BMSCs chondrogenic and cartilage regeneration.